SISTEME CLASICE IMPLICATE ÎN PROTEZAREA EDENTAŢIEI PARŢIAL ÎNTINSE - Magda-Ecaterina Antohe; Doriana Agop Forna; Monica Andronache; Norina Consuela Forna (Romanian Dental Association for Education, 2016)
The study aimed at individualizing the classic therapeutic methods of prosthesis treatments represented by the acrylic prosthesis as a temporary therapeutic method, with well defined roles, as well as by the classic skeletal prosthesis which uses crochets as maintenance, support and stabilization elements. The study lot comprised a number of 57 patients (aged between 30 and 82), reuniting various clinical entities in the field of dental prosthetics. The patients underwent complex clinical and paraclinical examinations that focused on a series of correlative aspects, with a deep practical impact with regard to the periodontal pathology, characterized by the multiple facets of a complex clinical picture. The classic systems are valid under any conditions of local, locoregional pathology, once the complications present at the level of the mucous-bony or dento-periodontal support are solved.